Compounding agent for rubber, rubber composition, and tire
The use of an inverse vulcanizate with terpene compounds in rubber compositions addresses the issue of low breaking strength in tires by forming a crosslinked structure that improves durability and stress resistance.
Patent Information
- Application Number
- JP2023097957
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-26
AI Technical Summary
Existing rubber compositions used in tires lack sufficient breaking strength, despite improvements in wear resistance and chipping resistance.
Incorporation of an inverse vulcanizate containing terpene compounds as a rubber compounding agent, with a topological polar surface area of 50 Ų and a high carbon-sulfur content, to form a crosslinked structure that enhances breaking strength and dispersibility.
The rubber composition exhibits improved breaking strength and reduced migration of the vulcanizing agent, resulting in enhanced durability and stress resistance.
Smart Images

Figure 2024179250000001 
Figure 2024179250000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a compounding agent for rubber, and a rubber composition and a tire each containing the compounding agent for rubber. [Background technology]
[0002] In recent years, rubber compositions used in rubber products such as tires are required to have further improved fracture properties in order to improve durability.
[0003] In response to such problems, Patent Document 1 describes a rubber composition having excellent abrasion resistance, for example, H(SCH2CH2OCH2CH2S) n Patent Document 2 describes a rubber composition containing a long-chain crosslinking agent represented by the formula -(CH2)2O(CH2)2-S as a rubber composition having excellent chipping resistance (elongation at break). x However, there is room for improvement in terms of breaking strength. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2005-507966 [Patent Document 2] JP 2019-19310 A [Patent Document 3] JP 2017-517603 A Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above, an object of the present invention is to provide a compounding agent for rubber capable of improving breaking strength.
[0006] The rubber compositions described in Patent Documents 1 and 2 do not contain an inverse vulcanizate. In addition, Patent Document 3 describes an inverse vulcanizate, but does not describe blending it as a vulcanizing agent in a rubber composition. [Means for solving the problem]
[0007] The present invention includes the embodiments set forth below. [1] Topological polar surface area of 50 Å 2 A compounding agent for rubber, comprising an inverse vulcanizate containing the following terpene compound as a raw material: [2] The rubber compounding agent according to [1], wherein the sum of the amount of carbon element and the amount of sulfur element contained in the inverse vulcanizate is 89 mass % or more. [3] The compounding agent for rubber according to [1] or [2], wherein the terpene compound contains zero or one heteroatom in one molecule. [4] The compounding agent for rubber according to any one of [1] to [4], wherein the terpene compound comprises at least one selected from the group consisting of limonene, farnesene, farnesol, myrcene, and squalene. [5] A rubber composition comprising the compounding agent for rubber according to any one of [1] to [4]. [6] A tire made using the rubber composition described in [5]. Effect of the Invention
[0008] According to an embodiment of the present invention, the breaking strength of a rubber composition can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, matters related to the implementation of the present invention will be described in detail.
[0010] The rubber compounding agent according to this embodiment has a topological polar surface area of 50 Å. 2The rubber compounding agent includes an inverse vulcanizate containing the following terpene compound as a raw material. That is, the rubber compounding agent includes an inverse vulcanizate synthesized using the terpene compound as a raw material. In this specification, the inverse vulcanizate refers to a structure in which chain sulfur is crosslinked with a small amount of organic matter, and is different from the inverse vulcanizate obtained by normal vulcanization in which polymer chains of organic matter are crosslinked with a small amount of sulfur.
[0011] The inverse vulcanizate is obtained by reacting an organic compound having two or more carbon-carbon double bonds with sulfur. For example, as shown in the following reaction formula, cyclic sulfur is converted into linear sulfur by heating. Then, the linear sulfur is mixed with an organic compound having two or more carbon-carbon double bonds and reacted to obtain an inverse vulcanizate. This reaction includes a nucleophilic addition reaction of a sulfur radical to a double bond. The temperature condition when mixing the linear sulfur with the organic compound is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 140°C or higher. If necessary, a catalyst such as a base or a metal salt may be used. [ka]
[0012] In the inverse vulcanizate, the sulfur chain splits during vulcanization of the rubber composition, and bonds to the polymer chain of the rubber component as a crosslinked structure containing carbon chains to form a crosslinked structure. The crosslinked chain becomes longer than the crosslinked structure consisting of only sulfur obtained by normal vulcanization due to the formation of a crosslinked structure containing carbon chains. As a result, it is believed that the flexibility of the rubber is improved and the breaking strength is improved. In addition, when stored as an unvulcanized rubber composition, since the inverse vulcanizate is a polymer, it is believed that it has lower migration and is less likely to bleed out than sulfur.
[0013] In this embodiment, among the inverse vulcanizates, a topological polar surface area of 50 Å 2 The inverse vulcanizate contains a terpene compound having a topological polar surface area of 50 Å or less as a raw material. 2It is preferable that the inverse vulcanizate containing the terpene-based chemical structure is obtained by reacting sulfur with an organic compound containing a terpene-based compound having a topological polar surface area of 50 Å or less. 2 Since a raw material with low polarity is used, which is as low as 1000 nm or less, it is believed that the dispersibility in the rubber composition is excellent. Therefore, it is believed that the crosslinking is uniform, which makes it possible to prevent stress concentration during strain deformation, and the breaking strength can be further improved. The topological polar surface area is preferably 30 Å or less. 2 More preferably, it is 25 Å or less. 2 is less than or equal to 0 Å 2 That's fine too.
[0014] Topological polar surface area (tPSA) refers to the area of the polar part of the surface of a molecule, and is defined as the sum of the surfaces of all polar atoms (mainly oxygen, nitrogen, and hydrogen bonded thereto). The topological polar surface area is a polar surface area that is approximately calculated only from the bonding pattern (topology) of atoms in a molecule without considering the three-dimensional structure of the molecule, and is calculated by the method described in Ertl P.et al., J.Med.Chem, 43 (2000), 3714-3717. Specifically, it can be calculated by a commercially available molecular structure editor software, and in this specification, the value calculated by ChemBioDraw Ultra (registered trademark) (version 13.0) provided by Revvity Signals Software, Inc. is used.
[0015] Terpene compounds are natural compounds whose structural unit is isoprene, and are used as a concept that includes not only terpenes, which are hydrocarbons whose structural unit is isoprene, but also terpenoids, which are derivatives having functional groups such as carbonyl groups and hydroxyl groups. Terpene compounds having two or more carbon-carbon double bonds in the molecule are preferred.
[0016] Topological polar surface area of 50 Å 2Examples of the terpene compounds include acyclic monoterpenes such as myrcene, citral, nerol, geraniol, geranyl nitrile, citral dimethyl acetal, geranyl acetone, and linalool, cyclic monoterpenes such as limonene, terpinene, terpinolene, perillaldehyde, phellandrene, dehydroxylinalool oxide, and carvone, sesquiterpenes such as farnesene, farnesol, nerolidol, bisabolol, nootkatone, germacrone, caryophyllene, and cadinene, diterpenes such as isophytol and geranyl-linalool, triterpenes such as squalene and lanosterol, and other terpenes such as solanesol, ionone, and methylionone. These can be used alone or in combination of two or more.
[0017] The terpene compound preferably has 0 or 1 heteroatom in one molecule. This makes the terpene compound less polar, and improves the dispersibility of the inverse vulcanizate in the rubber composition. Examples of the heteroatom include an oxygen atom, a nitrogen atom, a sulfur atom, a silicon atom, and a phosphorus atom, and the oxygen atom is preferred. The oxygen atom may be contained in the molecule of the terpene compound as, for example, a hydroxyl group or a carbonyl group.
[0018] In one embodiment, the terpene compound preferably includes at least one (X) selected from the group consisting of limonene, farnesene, farnesol, myrcene, and squalene. More preferably, the terpene compound includes at least one (Y) selected from the group consisting of farnesene, farnesol, and myrcene.
[0019] The organic compound used as the raw material of the inverse vulcanizate may be only the above-mentioned terpene compound, but may be used together with the terpene compound with other organic compounds having two or more carbon-carbon double bonds. The other organic compounds may have the above-mentioned heteroatoms, but are preferably those having no heteroatoms, i.e., hydrocarbons. The boiling point of the other organic compounds is not particularly limited, but is preferably 80°C or higher, more preferably 100°C or higher, and even more preferably 120°C or higher. The molecular weight of the other organic compounds is not particularly limited, but is preferably 100 to 3000, more preferably 100 to 500, and even more preferably 100 to 300.
[0020] Specific examples of organic compounds that may be used in combination with such terpene compounds include dicyclopentadiene (DCPD), diisopropenylbenzene (DIB), divinylbenzene (DVB), ethylene glycol dimethacrylate (EGDMA), 1,5,9-cyclododecatriene (CDDT), 5-vinyl-2-norbornene (VNB), 1,2,4-trivinylhexane (TVCH), tetraallyloxyethane, and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.
[0021] The organic compound used as the raw material for the inverse vulcanizate may be only one having two or more carbon-carbon double bonds, but may also be used in combination with an organic compound having one carbon-carbon double bond as long as the effect of the organic compound is not impaired.
[0022] In the organic compound used as a raw material for the inverse vulcanizate, the ratio of the terpene compound (preferably the above (X), more preferably the above (Y)) is preferably 40 to 100 mass%, more preferably 50 to 100 mass%, even more preferably 70 to 100 mass%, and even more preferably 90 to 100 mass%, relative to 100 mass% of the organic compound. The ratio of the terpene compound-derived component (preferably the above (X)-derived component, more preferably the above (Y)-derived component) relative to 100 mass% of the organic compound-derived component in the inverse vulcanizate is also preferably 40 to 100 mass%, more preferably 50 to 100 mass%, even more preferably 70 to 100 mass%, and even more preferably 90 to 100 mass%.
[0023] In one embodiment, the sum of the amount of carbon element and the amount of sulfur element contained in the inverse vulcanizate (total content ratio of carbon element and sulfur element) is preferably 89% by mass or more. The electronegativity of carbon is 2.55, and the electronegativity of sulfur is 2.58, and the electronegativity of both is very close. It is considered that the inverse vulcanizate has less polarity gap and is easily dispersed in the low polarity rubber component because the carbon element and the sulfur element are predominant, which leads to further improvement of the breaking strength. The sum of the amount of carbon element and the amount of sulfur element contained in the inverse vulcanizate is more preferably 90% by mass or more, and further preferably 91% by mass or more. The upper limit of the sum is not particularly limited, but may be, for example, 99% by mass or less, or 98% by mass or less.
[0024] In this specification, the contents of carbon and sulfur elements are values measured by a combustion method using an organic elemental analyzer, and the detailed measurement method is as described in the Examples section.
[0025] The carbon content in the inverse vulcanizate is not particularly limited, but is preferably 10 to 60 mass%, more preferably 15 to 50 mass%, and even more preferably 20 to 45 mass%. The sulfur content in the inverse vulcanizate is not particularly limited, but is preferably 30 to 89 mass%, more preferably 40 to 84 mass%, and even more preferably 45 to 79 mass%.
[0026] The mass ratio of the content of elemental sulfur to elemental carbon in the inverse vulcanizate (elemental sulfur / elemental carbon) is not particularly limited, but is preferably 1.0 to 10, more preferably 1.0 to 5.0, and even more preferably 1.1 to 4.0.
[0027] The inverse vulcanizate is preferably in a solid state at room temperature of 23° C. When it is in a solid state, it is easy to handle when preparing a rubber composition. Here, the term "solid state" means that it does not have flowability at room temperature of 23° C.
[0028] The glass transition point of the inverse vulcanizate is not particularly limited, but is preferably -50 to 60°C, more preferably -20 to 50°C, even more preferably -10 to 45°C, and even more preferably 0 to 45°C. When an inverse vulcanizate having a glass transition point of 60°C or less is used, the inverse vulcanizate melts when mixed with the rubber composition, and is easily dispersed uniformly in the rubber composition. In this respect, the melting point of sulfur used in normal vulcanization is 112.8°C, which is higher than the temperature at which it is mixed with the rubber composition. Here, the glass transition point is a value measured by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012 at a heating rate of 20°C / min (measurement temperature range: -100°C to 150°C).
[0029] The compounding agent for rubber according to the embodiment may be composed of only the inverse vulcanizate, or may contain additives generally compounded in rubber compositions together with the inverse vulcanizate. In one embodiment, the compounding agent for rubber may contain 30% by mass or more of the inverse vulcanizate, 50% by mass or more, 70% by mass or more, or 100% by mass. The compounding agent for rubber is used as a crosslinking agent (vulcanizing agent) because the inverse vulcanizate forms a crosslinked structure as described above. Therefore, in one embodiment, the compounding agent for rubber is a crosslinking agent (vulcanizing agent) for rubber.
[0030] The rubber composition according to the embodiment contains the compounding ingredients for rubber. The rubber composition preferably contains a diene rubber as a rubber component in addition to the compounding ingredients for rubber.
[0031] The diene rubber refers to a rubber having a repeating unit corresponding to a diene monomer having a conjugated double bond, and has a double bond in the polymer main chain. Specific examples of diene rubber include natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), nitrile rubber (NBR), chloroprene rubber (CR), butyl rubber (IIR), styrene-isoprene copolymer rubber, butadiene-isoprene copolymer rubber, and styrene-isoprene-butadiene copolymer rubber. These may be used alone or in combination of two or more. Among these, the diene rubber is preferably at least one selected from the group consisting of NR, IR, BR, and SBR. The diene rubber may include those modified at the ends or main chain as necessary (e.g., terminal-modified SBR) or those modified to impart desired properties (e.g., modified NR).
[0032] The content of the rubber compounding agent in the rubber composition is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, even more preferably 1 to 10 parts by mass, and even more preferably 2 to 8 parts by mass, relative to 100 parts by mass of the diene rubber, as the content of the inverse vulcanizate. The content of the inverse vulcanizate is preferably 0.05 to 16 parts by mass, more preferably 0.3 to 12 parts by mass, even more preferably 0.5 to 8 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the diene rubber, as the amount converted into sulfur.
[0033] A reinforcing filler may be blended in the rubber composition. Carbon black and / or silica are preferably used as the reinforcing filler. That is, the reinforcing filler may be carbon black alone, silica alone, or a combination of carbon black and silica. Preferably, carbon black alone or a combination of carbon black and silica is used. The content of the reinforcing filler is not particularly limited, and may be, for example, 10 to 140 parts by mass, 20 to 100 parts by mass, or 20 to 80 parts by mass relative to 100 parts by mass of the diene rubber.
[0034] The carbon black is not particularly limited, and various known types can be used. When carbon black is blended, the content thereof may be, for example, 5 to 100 parts by mass or 20 to 80 parts by mass per 100 parts by mass of the diene rubber.
[0035] The silica is not particularly limited, but wet silica such as wet precipitation silica and wet gel silica is preferably used. When silica is blended, the content may be, for example, 5 to 40 parts by mass or 5 to 30 parts by mass per 100 parts by mass of the diene rubber.
[0036] In addition to the above-mentioned components, the rubber composition according to the present embodiment may contain various additives that are generally used in rubber compositions, such as a silane coupling agent, zinc oxide, stearic acid, an antioxidant, wax, oil, and a vulcanization accelerator.
[0037] The rubber composition may or may not contain sulfur as a vulcanizing agent (crosslinking agent) in addition to the inverse vulcanizate. When the inverse vulcanizate and sulfur are used in combination, the content of the vulcanizing agent (total amount of the inverse vulcanizate and sulfur) is not particularly limited, but is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the diene rubber.
[0038] The vulcanization accelerator may be, for example, various vulcanization accelerators such as sulfenamide-based, thiuram-based, thiazole-based, and guanidine-based, and any one of them may be used alone or in combination of two or more. The content of the vulcanization accelerator is not particularly limited, but is preferably 0.1 to 7 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the diene rubber.
[0039] The rubber composition according to the present embodiment can be prepared by kneading in a conventional manner using a commonly used mixer such as a Banbury mixer, a kneader, a roll, etc. That is, for example, in the first mixing stage, other additives except for the vulcanizing agent (including the inverse vulcanizate) and the vulcanization accelerator are added and mixed with the diene rubber, and then, in the final mixing stage, the vulcanizing agent (including the inverse vulcanizate) and the vulcanization accelerator are added and mixed with the obtained mixture to prepare the rubber composition.
[0040] The rubber composition thus obtained can be used for various rubber products such as tires, anti-vibration rubber, conveyor belts, etc. When the rubber composition is used for tires, it can be used as tread rubber or sidewall rubber for pneumatic tires of various applications and sizes such as tires for passenger cars and large tires (heavy load tires) for trucks and buses.
[0041] The rubber composition is molded into a predetermined shape by a conventional method, for example, extrusion processing, and heated and vulcanized to form a vulcanized rubber. When the rubber composition is used for a tire, the tire can be manufactured by molding the rubber composition into a predetermined shape by extrusion processing or the like, combining the rubber composition with other parts to prepare a green tire, and then vulcanizing the green tire at, for example, 130 to 190°C. EXAMPLES
[0042] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0043] The topological polar surface areas (tPSA) of the organic compounds used as raw materials in the following Synthesis Examples A to H are as follows. Farnesol: 20.23Å 2 Ethylene glycol dimethacrylate: 52.6Å 2 Other organic compounds: 0Å 2 (Because it does not contain heteroatoms)
[0044] The carbon and sulfur element contents of the inverse vulcanizates A to H synthesized in Synthesis Examples A to H were measured by the combustion method using an organic elemental analyzer. The organic elemental analyzer "vario MACRO cube" (manufactured by Elementor Japan Co., Ltd.) was used for the measurements, and the measurement conditions were gas: helium, oxygen, standard substance: sulfanilamide, combustion tube temperature: 1150°C, reduction tube temperature: 850°C.
[0045] [Synthesis example A] 2.5g of sulfur was added to a glass container and stirred at 165°C for 15 minutes. After confirming that the sulfur had dissolved, 0.5g of dicyclopentadiene and 2.0g of (+)-limonene were added and further stirred at 165°C for 30 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 140°C for 16 hours to obtain an inverse vulcanizate A. When the obtained inverse vulcanizate A was subjected to elemental analysis, the carbon content was 31% by mass, the sulfur content was 66% by mass, and the sum of the two was 96% by mass. The glass transition point of the inverse vulcanizate A was 29°C.
[0046] [Synthesis example B] 4.0 g of sulfur was added to a glass container and stirred at 165°C for 15 minutes. After confirming that the sulfur had dissolved, 0.5 g of dicyclopentadiene and 0.5 g of (+)-limonene were added and further stirred at 165°C for 30 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 140°C for 16 hours to obtain an inverse vulcanizate B. When the obtained inverse vulcanizate B was subjected to elemental analysis, the carbon content was 22% by mass, the sulfur content was 76% by mass, and the sum of the two was 97% by mass. The glass transition point of the inverse vulcanizate B was 17°C.
[0047] [Synthesis example C] 4.0 g of sulfur was added to a glass container and stirred at 175°C for 15 minutes. After confirming that the sulfur had dissolved, 2.5 g of trans-β-farnesene was added and stirred at 175°C for an additional 60 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 140°C for 16 hours to obtain inverse vulcanizate C. Elemental analysis of the obtained inverse vulcanizate C revealed that the carbon content was 42% by mass, the sulfur content was 50% by mass, and the sum of the two was 92% by mass. The glass transition point of inverse vulcanizate C was 16°C.
[0048] [Synthesis example D] 4.0 g of sulfur was added to a glass container and stirred at 175°C for 15 minutes. After confirming that the sulfur had dissolved, 2.5 g of farnesol was added and stirred at 175°C for an additional 60 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 140°C for 16 hours to obtain an inverse vulcanizate D. When the obtained inverse vulcanizate D was subjected to elemental analysis, the carbon content was 38% by mass, the sulfur content was 53% by mass, and the sum of the two was 91% by mass. The glass transition point of the inverse vulcanizate D was 21°C.
[0049] [Synthesis example E] 2.5g of sulfur was added to a glass container and stirred at 175°C for 15 minutes. After confirming that the sulfur had dissolved, 2.5g of myrcene was added and stirred at 175°C for an additional 60 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 140°C for 16 hours to obtain an inverse vulcanizate E. When the obtained inverse vulcanizate E was subjected to elemental analysis, the carbon content was 39% by mass, the sulfur content was 54% by mass, and the sum of the two was 92% by mass. The glass transition point of the inverse vulcanizate E was 0°C.
[0050] [Synthesis example F] 3.0 g of sulfur was added to a glass container and stirred at 165°C for 15 minutes. After confirming that the sulfur had dissolved, 2.0 g of squalene was added and stirred at 165°C for an additional 45 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 140°C for 16 hours to obtain an inverse vulcanizate F. When the obtained inverse vulcanizate F was subjected to elemental analysis, the carbon content was 31% by mass, the sulfur content was 64% by mass, and the sum of the two was 95% by mass. The glass transition point of the inverse vulcanizate F was 35°C.
[0051] [Synthesis example G (comparative example)] 4.0 g of sulfur was added to a glass container and stirred at 165°C for 15 minutes. After confirming that the sulfur had dissolved, 1.5 g of ethylene glycol dimethacrylate and 1.0 g of dicyclopentadiene were added and further stirred at 165°C for 30 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 140°C for 16 hours to obtain an inverse vulcanizate G. When the obtained inverse vulcanizate G was subjected to elemental analysis, the carbon content was 32% by mass, the sulfur content was 56% by mass, and the sum of the two was 88% by mass.
[0052] [Synthesis example H (comparative example)] 4.0 g of sulfur was added to a glass container and stirred at 120°C for 15 minutes. After confirming that the sulfur had dissolved, 2.5 g of divinylbenzene (mixture of isomers) was added and stirred at 120°C for an additional 30 minutes. After confirming that the color of the solution had changed, the solution was poured into a silicon mold. Then, the solution was heated in an oven at 120°C for 48 hours to obtain inverse vulcanizate H. Elemental analysis of the obtained inverse vulcanizate H revealed that the carbon content was 12% by mass, the sulfur content was 86% by mass, and the sum of the two was 98% by mass.
[0053] [Preparation of Rubber Composition] Using an internal mixer, in accordance with the formulation (parts by mass) shown in Table 1 below, at the first mixing stage, the vulcanizing agent (including inverse vulcanizate) and other compounding ingredients excluding the vulcanization accelerator were added to the diene rubber and kneaded (discharge temperature = 160°C). Next, at the final mixing stage, the vulcanizing agent and the vulcanization accelerator were added to the kneaded product obtained and kneaded (discharge temperature = 90°C) to prepare a rubber composition. Details of each component in Table 1 are as follows.
[0054] SBR: JSR Corporation "SBR1502" ·NR:RSS#3 Carbon black: Cabot Japan Co., Ltd. "Show Black N330T" Zinc oxide: "Zinc oxide type 3" manufactured by Mitsui Mining & Smelting Co., Ltd. Stearic acid: Kao Corporation's "Lunac S-20" Sulfur: "Powdered sulfur" manufactured by Tsurumi Chemical Industry Co., Ltd., sulfur content = 95% by mass Inverse vulcanizates A to H: Inverse vulcanizates obtained in the above Synthesis Examples A to H Vulcanization accelerator: "Noccela CZ-G (CZ)" manufactured by Ouchi Shinko Chemical Co., Ltd.
[0055] [Evaluation of Rubber Composition] Each rubber composition thus obtained was vulcanized at 160° C. under pressure using a metal plate as a mold to prepare a vulcanized rubber sample. The vulcanization time was determined based on the 90% vulcanization time (t90) previously measured for each rubber composition in accordance with JIS K6300-2:2001.
[0056] The obtained vulcanized rubber samples were subjected to a tensile test according to the following method to evaluate the fracture properties.
[0057] Tensile strength at break: A tensile test was conducted in accordance with JIS K6251:2017 to measure the tensile strength at break. No. 7 dumbbells were used as test pieces. The results for Comparative Examples 2-3 and Examples 1-7 are expressed as an index with the value for Comparative Example 1 set to 100, and the results for Example 8 are expressed as an index with the value for Comparative Example 4 set to 100. A larger index indicates a higher tensile strength at break and better breaking strength.
[0058] Elongation at break: A tensile test was conducted in accordance with JIS K6251:2017 to measure the elongation at break. No. 7 dumbbells were used as test pieces. The results for Comparative Examples 2 to 3 and Examples 1 to 7 are expressed as an index with the value for Comparative Example 1 set to 100, and the results for Example 8 are expressed as an index with the value for Comparative Example 4 set to 100. A larger index indicates a larger elongation at break and better fracture properties.
[0059] [Table 1]
[0060] The results are shown in Table 1. Examples 1 to 7, in which inverse vulcanizates A to F, which were synthesized using terpene compounds with small topological polar surface areas as raw materials, were blended as vulcanizing agents, had higher tensile strength at break and elongation at break, and were superior in breaking strength, compared to Comparative Example 1, in which sulfur was used as a vulcanizing agent. Example 8 was superior in breaking strength to Comparative Example 4.
[0061] In contrast, in Comparative Example 2, which contained inverse vulcanizate G synthesized from an organic compound with a large topological polar surface area, the elongation at break was superior to that of Comparative Example 1, but the tensile strength at break was significantly lower and the breaking strength was inferior. In Comparative Example 3, which contained inverse vulcanizate H, which had a small topological polar surface area but was made from an organic compound that was not a terpene compound, the tensile strength at break was superior, but the elongation at break was inferior.
[0062] In addition, the various numerical ranges described in the specification can be arbitrarily combined with their upper and lower limits, and all such combinations are considered to be preferred numerical ranges described in the specification. In addition, a numerical range described as "X to Y" means from X to Y.
Claims
1. Topological polar surface area is 50 Å 2 A compounding agent for rubber, comprising an inverse vulcanizate containing the following terpene compound as a raw material:
2. 2. The rubber compounding agent according to claim 1, wherein the sum of the amount of carbon element and the amount of sulfur element contained in the inverse vulcanizate is 89 mass % or more.
3. 2. The compounding agent for rubber according to claim 1, wherein the terpene compound contains zero or one heteroatom in one molecule.
4. 2. The rubber compounding agent according to claim 1, wherein the terpene compound comprises at least one selected from the group consisting of limonene, farnesene, farnesol, myrcene, and squalene.
5. A rubber composition comprising the compounding agent for rubber according to any one of claims 1 to 4.
6. A tire made using the rubber composition according to claim 5.
Citation Information
Patent Citations
Elastomeric polymer with long chain cross-links for improved abrasion resistance
JP2005507966A
Sulfur composites and polymer materials derived from elemental sulfur
JP2017517603A
Rubber composition and pneumatic tire
JP2019019310A
